2010
DOI: 10.1590/s0102-33062010000100006
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade polínica das Mimosoideae (Leguminosae) ocorrentes em uma área de caatinga, Pernambuco, Brasil

Abstract: RESUMO -(Diversidade polínica das Mimosoideae (Leguminosae) ocorrentes em uma área de caatinga, Pernambuco, Brasil). O município de Mirandiba, Pernambuco, considerado prioritário para a conservação da caatinga, apresenta cerca de 25% das espécies de Leguminosae do bioma, sendo 23 espécies em 13 gêneros da subfamília Mimosoideae, das quais 6 espécies são endêmicas. Dezenove táxons desta subfamília tiveram seus grãos de pólen caracterizados por microscopia óptica e eletrônica de varredura, ilustrados e incluídos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 15 publications
3
10
1
8
Order By: Relevance
“…The pollen data obtained in our study as well as by other authors (Caccavari, 1988;Grether, 1997;Lima et al, 2008;Buril et al, 2010) do not support the monophyly of Leiocarpae, providing additional evidence for the grouping found by Simon et al (2011) (Figure 4). This series is highly heterogeneous with respect to number of grains per polyad and polyad size and shape, and two obvious groups were observed (Figure 4).…”
Section: J Santos-silva Et Alcontrasting
confidence: 52%
See 3 more Smart Citations
“…The pollen data obtained in our study as well as by other authors (Caccavari, 1988;Grether, 1997;Lima et al, 2008;Buril et al, 2010) do not support the monophyly of Leiocarpae, providing additional evidence for the grouping found by Simon et al (2011) (Figure 4). This series is highly heterogeneous with respect to number of grains per polyad and polyad size and shape, and two obvious groups were observed (Figure 4).…”
Section: J Santos-silva Et Alcontrasting
confidence: 52%
“…The genus contains approximately 540 species (Simon et al, 2011), about 38% of which have been analysed to date (Erdtman 1945(Erdtman , 1952Van Campo & Guinet, 1961;Barros, 1966;Guinet, 1969;Sorsa, 1969;Barth, 1973;Silvestre-Capelato & Melhem, 1997;Caccavari, 1985Caccavari, , 1986aCaccavari, , 1986bCaccavari, , 1987Caccavari, , 1988Caccavari, , 1989Grether & Martínez-Bernal, 1996;Grether, 1997;Martínez-Bernal, 2006;Flores-Cruz et al, 2006;Lima et al, 2008;Buril et al, 2010). These studies revealed the group's diverse pollen morphology with respect to grain number per polyad (4, 8, 12 or 16), and polyad size and shape, characterising Mimosa as a eurypalynous genus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A subfamília Mimosoideae foi tratada anteriormente por Buril et al (2010). um mosaico vegetacional, variando desde campos abertos até uma caatinga arbórea, foi tratado durante muitos anos como uma região em avançado estágio de degradação tal quais os municípios circunvizinhos, entretanto, hoje é considerado como área prioritária para a conservação da Caatinga ( Fig.…”
Section: Introductionunclassified